Arthroscopic Reconstruction of Posterior Cruciate Ligament with Embedded Tibial Tendon Bolt - Hua‐zhe Li; Cong Yu; Zhi‐tao Zhang; Shi Yan; Yun‐jian Liao; Dai‐feng Lu (Orthopaedic Surgery, 2021)
Objective To evaluate the effect of newly designed arthroscopic reconstruction of posterior cruciate ligament (PCL) using tibial tendon bolt. Methods The effects of embedded tendon pin were observed by X‐ray of knee joint. From October 2010 to September 2015, 51 PCL injury patients who met the inclusion criteria were enrolled in this retrospective study. The arthroscopically assisted reconstruction of the PCL with tibial tendon bolt was performed on all patients. Visual Analog Scale (VAS) pain score, Tegner activity score, Lysholm score, International Knee Documentation Committee (IKDC) assessment, posterior drawer test (PDT), and KT‐1000 activity score were evaluated preoperatively and at 1‐year postoperative and 3‐year postoperative. Results The preoperative, 1‐year postoperative, and 3‐year postoperative IKDC score (15.8% ± 14.8%, 89.6% ± 5.8%, and 86.8% ± 5.4%), Lysholm score (17.4 ± 10.7, 91.2 ± 2.8, and 88.2 ± 3.1), VAS score (5.8 ± 1.2, 1.3 ± 0.5, and 0.6 ± 0.5), Tegner activity score (1.2 ± 0.8, 8.1 ± 0.8, and 7.4 ± 0.8), and KT‐1000 score (15.6 ± 3.6, 4.5 ± 2.4, and 5.4 ± 1.8) were obtained. There were significant differences in these outcomes among preoperative, 1‐year postoperative, and 3‐year postoperative (all P < 0.0001). After 1‐ and 3‐year surgery, 31 (60.8%) and 26 (51.0%) patients had the negative PDT, indicating that the PCL injury was improved. There were no postoperative complications. Conclusion The application of tendon pin fixed by tibial inlay 8‐shaped tibial tunnel to reconstruct PCL was an effective, simple, and safe surgical procedure for PCL injury.